Mechanism and regulation of LCST behavior in poly(hydroxypropyl acrylate)-based temperature-sensitive hydrogels. Issue 35 (23rd August 2022) - Chen, Fuping; Lu, Guoqiang; Yuan, Hengda; Li, Ruiqi; Nie, Jun; Zhao, Yingying; Shu, Xin; Zhu, Xiaoqun
Abstract : The transformation mechanism of PHPA-based temperature-sensitive hydrogels showed the water molecules agglomerated into larger clusters, then light was incident at the water clusters, which resulted in the hydrogels changing to an opaque state. Abstract : The hydrogels with the LCST (low critical solution temperature) behavior undergo dramatic changes at their transition temperature due to phase separation, such as volume contraction or loss of permeability on warming. Hydrogels with this character have been used extensively in drug delivery, flexible devices, temperature-sensitive robotics, etc. How to regulate the transition behavior of LCST-type hydrogels has been the direction of continuous efforts of researchers. In this paper, a series of changes of PHPA hydrogels that occurred in temperature-sensitive hydrogels were discussed. The results showed that when the temperature increased the hydrogen bond between the polymer and water was broken and the water aggregated into water clusters. The hydrogen bond between water and the polymer and the mobility of the polymer molecular chains played a decisive role in the phase transition of PHPA hydrogels. To modulate the LCST behaviour of the PHPA hydrogels, different concentrations and types of ions, crosslinkers and co-solvents were added to the precursor solution to modify the state of water and the moving ability of the molecular chains. The resulting PHPA hydrogels had a wide LCST range (6–40 °C), adjustable transition rates (0.17–7% s −1 ) and broad transition windows (2.6–24.6 °C). This modulation method can expand the application of PHPA hydrogels, and also provide a reference for the regulation of other LCST hydrogels.